Evolution of oxygen functionalities in graphene oxide and its impact on structure and exfoliation: An oxidation time based study - Colavita, Paula (My University, 2018)
Control over oxygen functionalities is important for the realization of Graphene Oxide (GO) based applications. Evolution of oxygen functionalities with time of oxidation and its impact on GO structure, exfoliation and reduction is investigated using XRD, FTIR, XPS, TGA and AFM. The results indicate no net increase in oxygen bound carbon atoms compared to graphitic carbon within the samples studied. However the percentage contributions from each type of oxygen functionalities tend to vary as the oxidation progress. Changes in the thermogravimetric response were observed with continued oxidation that showed a change from one mass loss region to two mass loss regions. The interaction kinetics of the protective group and the spatial distribution of oxygen functionalities during graphite oxidation give key insight to the above observed properties in GO. It is also shown that the observed changes in the structure have a direct impact on the ability to exfoliate GO to single layers as well as on the reduction process to produce reduced graphene oxide (rGO). These results are significant in the scalable production of GO with controlled and consistent quality for applications in the areas such as chemical and biological sensing, water purification and development of nanocomposites.
PUBLISHED
Keywords: Graphene oxide; Oxygen functionalities; Structure; Exfoliation; Thermal reduction; Nanoscience & Materials